INFLUENCE OF CORE SERVICE AND SERVICE ENCOUNTER FAILURES AS INCIDENTS OF SWITCHING COSTS ON CUSTOMER RETENTION IN FOOD SERVICE ESTABLISHMENTS IN UMUAHIA, ABIA STATE - Anyanwu, Iheanyi Bona (African Journal of Social and Behavioural Sciences, 2022)
This study sought to determine the influence of core service and service encounter failures as incidents of switching costs on customer retention in food service establishments in Umuahia metropolis Abia State. It was a descriptive survey research in which two specific objectives and two research hypotheses guided the study. The researcher purposively used 300 customers of six reputable food service establishments in the study area as sample size. The research instrument used for data collection was a questionnaire on a 4-point scale which was subjected to reliability test that produced a reliability co-efficient of 0.79 proving the usability of the instrument, while accessibility sampling technique was used in the administration of the instrument. Descriptive and inferential statistics on SPSS version 24 were used to analyze the data generated. Findings revealed that core service failure did not significantly influence customer retention in the study area as indicated by adjusted R square value of 0.113 and F value of 0.818 significant at p=0.000F. Conversely, service encounter failure as incident of switching costs was found to have a significant influence on customer retention in the study area as indicated by adjusted R square value of 0.616 and F value of 4.864 significant at p=0.000F. On the strength of the findings, it is concluded that core service and service encounter failures as incidents of switching costs can influence customer retention in food service establishments in Umuahia. In view of the foregoing, it is recommended that operators of food service establishments are to ensure that there is continuous improvement in the functional and technical aspects of their operations to mitigate core service failures and that service providers should be regularly trained to enhance their skills, service orientation, and improve service provider-service consumer relationship thereby mitigating service encounter failures.